2021
DOI: 10.1021/acsomega.0c05604
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Titanate-Modified Graphene Oxide as Friction and Wear Reduction Additives in PAO Oil

Abstract: Diacetoxy-stearoyloxy-titanium-modified graphene oxide (Titanate-GO) was successfully prepared using titanium tetraisopropanolate, stearic acid, acetic acid, and graphene oxide (GO). The morphology and structure of the as-prepared materials were tested by FT-IR, Raman, TG/ DSC, SEM, and TEM instruments. The results indicate that long alkyl titanium chains have been grafted on the surface of a GO sheet, which guaranteed the dispersibility of Titanate-GO in PAO10 base oil. Then, the lubrication properties of Tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Many researchers have investigated the tribological properties of graphene oxide (GOs) as additives in water and lubrication oil. Although the size of the GO can exceed 10 μm, its thickness is less than 1 nm. Thus, it is considered to enter narrow friction interfaces under boundary lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have investigated the tribological properties of graphene oxide (GOs) as additives in water and lubrication oil. Although the size of the GO can exceed 10 μm, its thickness is less than 1 nm. Thus, it is considered to enter narrow friction interfaces under boundary lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…1 In recent years, with the development of nanotechnology, nanofluids containing nanoparticles in the size of 1-100 nm have attracted increasing attention as lubricants for metal-forming, such as TiO 2 , 2 CuO, 3 MoS 2 , 4 SiO 2 , 5 and graphene oxide. 6 These nanoparticles exhibit superior frictionreduction and anti-wear performance in water-based fluids. Besides, water-based nanofluids have excellent colling performance and low pollution compared to oilbased lubricants, 7 which are of great prospect as environmental-friendly lubricants for hot rolling lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…However, friction and wear are inevitable during hot rolling process, which will seriously impact the metal surface quality, increase energy consumption and material wastage 1 . In recent years, with the development of nanotechnology, nanofluids containing nanoparticles in the size of 1–100 nm have attracted increasing attention as lubricants for metal‐forming, such as TiO 2 , 2 CuO, 3 MoS 2 , 4 SiO 2 , 5 and graphene oxide 6 . These nanoparticles exhibit superior friction‐reduction and anti‐wear performance in water‐based fluids.…”
Section: Introductionmentioning
confidence: 99%
“…With its extremely low coefficient of friction, atomic smooth surface, and low interlayer shear resistance, graphene has attracted considerable attention of many scholars in the field of lubrication, especially as a nanoadditive to improve the tribological properties of polymers. , Since graphene is extremely easy to agglomerate and difficult to disperse in most solvents, surface modification of graphene by chemical modification is crucial to improve the dispersion and stability of graphene in the polymer matrix. Mo et al used KH550 to modify GO to obtain functionalized GO (FGO) with good dispersibility and compatibility in the polyurethane matrix. The results showed that the friction and corrosion resistance of the composite coating with 0.25–0.5% FGO are the best …”
Section: Introductionmentioning
confidence: 99%